Model Pengamanan Kendaraan dengan Sistem Kontrol Jarak Jauh dan GPS - Arthur Daniel Limantara; Tjahjaning Tingastuti Surjosuseno; Bambang Subiyanto; Muhammad Ikhsan Setiawan; Nawir Rasidi (CAHAYAtech, 2021)
A